Notes on the Australian Anacaenini (Coleoptera: Hydrophilidae): description of male of Phelea breviceps Hansen and unravelling the identity of Crenitis neogallica Gentili - Fikáček, Martin; Watts, Chris H. S. (Zootaxa, 2015)
The holotype and additional specimens of the Tasmanian endemic Phelea breviceps Hansen, 1999, and the holotype of Crenitis neogallica Gentili, 1996 were examined in order to explore their generic and tribal placement. The morphology of Phelea is illustrated in detail, its male genitalia are described for the first time, and it is confirmed as a member of Anacaenini, sharing numerous characters with Crenitis Bedel, 1881 and the New Zealand endemic Horelophus walkeri Orchymont, 1913. Crenitis neogallica is removed from Anacaenini and transferred to the rygmodine genus Pseudohydrobius Blackburn, 1898 (as Pseudohydrobius neogallicus (Gentili, 1996) comb. nov.) and its holotype is illustrated. The genus Crenitis is hence removed from the Australian fauna.